Convocation bound - Siti Sarah, Mohamad Rajimi (2017)
Kuantan, 19 Nov – The determination of a stroke victim to show up and received his Diploma at the University Malaysia Pahang (UMP) 12th Convocation Ceremony has captured the imagination of all who were presence.